KAJIAN PENERIMAAN KONSUMER TERHADAP IKAN ASAP SELAIS (Cryptoperus bicirchis) YANG DIBUAT MENGUNAKAN ASAP CAIR - Desmelati Desmelati; Mirna Ilza; Nuzirwan Nuzirwan (Fakultas Perikanan dan Kelautan, Universitas Riau, 2013)
The research was conducted to observe the consumer acceptance on thesmoke flavoured fish Selais (Cryptoperus bicirchis). The fresh fish was preparedby eviscerated and washed it with clean freshwater. The fish was soaked in liquidsmoke solution at the concentration of 2%, 4%, 6%, or 8% for 30, 60, or 90minutes. Then, the fish was dried in the artificial dryer at temperature 50 – 60 0Cuntil the weight was reduced up to 70% of the initial weight. The smoke flavoredfish yielded was evaluated by determining their consumer acceptance, pH value,content of total acid and content of total phenol. The result showed that the fishsoaked in the liquid smoke at the concentration of 6% for 60 minutes is the mostlyaccepted by consumers, indicated on the highest value of consistence, texture,odor and flavor. The pH value, content of total acid and content of total phenol are6,40, 0,269%, and 0,84%, respectively.Keywords: consumer acceptance, Cryptoperus bicirchis, liquid smoke, andsmoke flavoured fish